Study of the Mechanical Properties of Gypsum Tuff –Dunes Sand Mixture for use in Saharan Road Construction - Khelllou, Abderrezak; Abdelouahed, Kriker; Abdelatif, Hafsi; Khadija, Mokhtari; Hind, Siad (International Journal of Integrated Engineering, 2021)
This work fits into the context of minimizing the use of non-renewable and depleting natural resources, such as gypsum tuff. Its objectives are to study the mechanical properties of a mixture of gypsum tuff (GT) and sand dunes (SD) in order to have the possibility of integrating it into Saharan pavements. The results obtained showed an improvement of Bearing index (Immediate bearing index, IBI and Bearing index after soaking, IBas ), evaluated by the CBR test, of the mixture composed of 80% of GT + 20% SD in comparison with that of the gypsum tuff  alone. Whereas its simple compressive strength decreased slightly at the age of 28 days. This decrease led us to treat the mixture with lime and to examine the evolution of the compressive strength according to the curing time.